Molecular Pathology and Pharmacological Treatment of Autism Spectrum Disorder-Like Phenotypes Using Rodent Models - Kuo, Hsiao-Ying; Liu, Fu-Chin (Frontiers in Cellular Neuroscience, 2018)
Autism spectrum disorder (ASD) is a heterogeneous neurodevelopmental disorder with a high prevalence rate. The core symptoms of ASD patients are impaired social communication and repetitive behavior. Genetic and environmental factors contribute to pathophysiology of ASD. Regarding environmental risk factors, it is known that valproic acid (VPA) exposure during pregnancy increases the chance of ASD among offspring. Over a decade of animal model studies have shown that maternal treatment with VPA in rodents recapitulates ASD-like pathophysiology at a molecular, cellular and behavioral level. Here, we review the prevailing theories of ASD pathogenesis, including excitatory/inhibitory imbalance, neurotransmitter dysfunction, dysfunction of mTOR and endocannabinoid signaling pathways, neuroinflammation and epigenetic alterations that have been associated with ASD. We also describe the evidence linking neuropathological changes to ASD-like behavioral abnormalities in maternal VPA-treated rodents. In addition to obtaining an understanding of the neuropathological mechanisms, the VPA-induced ASD-like animal models also serve as a good platform for testing pharmacological reagents that might be use treating ASD. We therefore have summarized the various pharmacological studies that have targeted the classical neurotransmitter systems, the endocannabinoids, the Wnt signal pathway and neuroinflammation. These approaches have been shown to often be able to ameliorate the ASD-like phenotypes induced by maternal VPA treatments.